Removal of Common Warts by High-Intensity Focused Ultrasound: An Introductory Observation - Torsten Bove; Tomasz Zawada; Alexander Jessen; Mattia Poli; Jørgen Serup (Case Reports in Dermatology, 2021)
Therapies of common warts are cumbersome and not very effective. Recurrences are common. A new 20 MHz high-intensity focused ultrasound (HIFU) method is introduced as a new potential treatment modality. With HIFU, selected targets in the epidermis and dermis can be treated with full control of the depth and position of the ultrasound lesion and the energy applied to the target. The treatment can be monitored directly in real-time via an integrated dermoscope in the ultrasound probe. Two warts were treated with 8–10 shoulder-by-shoulder treatment doses, focal depth 1.3 mm, and 1.2 J/dose. Pretreatment ultrasound B-mode scanning had shown the thickness and depth of the warts. The treated areas developed a dry wound covered by a crust over the next 1–2 days. After 2 weeks the skin was healed, with no wart and no scar. Observation showed no reoccurrence. HIFU has future potential for treatment of common warts and flat warts, and a broad range of skin lesions being logic further candidates for targeted ablative treatment. One single treatment may suffice. It is, therefore, a new modality in dermatology with a large range of indications.